Catalytic combustion type optical fiber Bragg grating hydrogen gas sensor using platinum-loaded fumed silica powder. (22nd March 2023) - Okazaki, Shinji; Kawada, Hiroyuki; Koshiba, Yusuke; Kasai, Naoya; Maru, Yusuke; Mizutani, Tadahito; Takesaki, Yuichiro; Shimano, Satoshi
Abstract: In order to ensure the safety of hydrogen energy system, a robust and reliable hydrogen sensor device with an optical fiber Bragg grating (FBG) has been developed. The sensing mechanism is based on temperature changes in the device induced by the heat of the catalytic reaction of hydrogen on platinum-loaded fumed silica catalyst powder. Through optimization of the preparation conditions for the catalyst, which is a hydrogen-sensitive substance, a large degree of heat generation in the presence of hydrogen could be obtained, and good stability was also achieved. A sensor device in which a column filled with the obtained catalyst powder was attached to a commercially available robust FBG for temperature measurement, and integrated with another FBG as a temperature reference via a heat shielding plate, was fabricated and evaluated. A stable baseline was demonstrated even in an environment where the ambient temperature severely fluctuated, and a sensor output proportional to the hydrogen concentration could be obtained. The detection limit was about 0.2 vol%, and the long-term stability of the device was good. Highlights: Platinum-loaded fumed silica catalyst was prepared as hydrogen sensing materials. Large amount of catalytic combustion heat of hydrogen on the catalyst was obtained. The catalyst was immobilized on robust fiber Bragg grating temperature sensor device. The sensor integrated with temperature compensation device showed good responses. The detection limit was about 0.2 vol% and the long-term stability was good.